2023
DOI: 10.3390/f14112135
|View full text |Cite
|
Sign up to set email alerts
|

Native Bamboo (Indosasa shibataeoides McClure) Invasion of Broadleaved Forests Promotes Soil Organic Carbon Sequestration in South China Karst

Zedong Chen,
Xiangyang Xu,
Zhizhuang Wu
et al.

Abstract: Bamboo invasion into broadleaf forests is a common phenomenon in karst areas; however, the effect of bamboo invasion on soil organic carbon (SOC) in karst areas and the mechanism of the effect are not clear. We selected the study site with broad-leaved forests (BF), mixed forests (MF), and pure bamboo (Indosasa shibataeoides McClure) forests (IF). Furthermore, we sampled the soil from 0 cm to 20 cm and 20 cm to 40 cm layers in the region and investigated the soil properties, organic carbon fractions, and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Bamboo and wood-mixed planting promotes the establishment of multi-storey forests, which helps to enhance the ecological function of single-storey forests [14,15]. Studies have shown that bamboo-tree mixtures can increase the total aboveground biomass, including arborous (tree and Moso bamboo) biomass [16]; enhance litterfall biomass per unit area; improve fungal community structure [17]; and boost the abundance of arbuscular mycorrhizal fungi (AMF) in the soil [18]. The mixing ratio of Moso bamboo to broadleaf trees impacts the physical and chemical properties of the soil, indirectly influencing the soil bacterial community [19].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo and wood-mixed planting promotes the establishment of multi-storey forests, which helps to enhance the ecological function of single-storey forests [14,15]. Studies have shown that bamboo-tree mixtures can increase the total aboveground biomass, including arborous (tree and Moso bamboo) biomass [16]; enhance litterfall biomass per unit area; improve fungal community structure [17]; and boost the abundance of arbuscular mycorrhizal fungi (AMF) in the soil [18]. The mixing ratio of Moso bamboo to broadleaf trees impacts the physical and chemical properties of the soil, indirectly influencing the soil bacterial community [19].…”
Section: Introductionmentioning
confidence: 99%